Fast Determination of Ethylendiamine in Aminophylline Tablets by Small‐sized Capillary Electrophoresis with Amperometric Detection. Issue 4 (3rd April 2013) - Ge, Jinyuan; Tong, Fanghong; Li, Ying; Zhang, Yang; Chu, Qingcui; Ye, Jiannong
Abstract A novel method for fast determination of ethylendiamine (EDA) in Aminophylline Tablets has been developed by small‐sized capillary electrophoresis with amperometric detection (small‐CE‐AD) coupled with field‐amplified sample injection (FASI). Under the optimum conditions, EDA and four aliphatic diamine homologs (1, 3‐diaminopropane, 1, 4‐diaminobutane, 1, 5‐diaminopentane and 1, 6‐diaminohexane) could be well separated within 6 min at a separation voltage of 2.0 kV in an acetate buffer solution of pH 3.8 with low limit of detection (LOD) of 1.3×10−11 g/mL for EDA (S/N=3). The proposed method has been successfully applied to direct determination of EDA content in different batches of Aminophylline Tablets. The method does not require off‐line preconcentration and derivatization steps, which should find wide application fields including pharmaceuticals as an alternative to conventional and microchip CE approaches.